The role of visual processing on tactile suppression - Gertz, Hanna; Fiehler, Katja; Voudouris, Dimitris; Justus Liebig University Giessen (My University, 2018)
It has been suggested that tactile signals are suppressed on a moving limb to free capacities for processing other relevant sensory signals. In line with this notion, we recently showed that tactile suppression is indeed stronger in the presence of reach-relevant somatosensory signals. Here we examined whether this effect also generalizes to the processing of additional visual signals during reaching. Brief vibrotactile stimuli were presented on the participantsâ right index finger either during right-hand reaching to a previously illuminated target LED, or during rest. Participants had to indicate whether they detected the vibrotactile stimulus or not. The target LED remained off (tactile), or was briefly illuminated (tactile & vis) during reaching, providing additional reach-relevant visual information about the target position. If tactile suppression frees capacities for reach-relevant visual information, suppression should be stronger in the tactile & vis compared to the tactile condition. In an additional visual-discrimination condition (tactile & visDis), the target LED flashed once or twice during reaching and participants had to also report the number of flashes. If tactile suppression occurs to free additional capacities for perception-relevant visual signals, tactile suppression should be even stronger in the tactile & visDis compared to the tactile & vis condition. We found that additional visual signals improved reach endpoint accuracy and precision. In all conditions, reaching led to tactile suppression as indicated by higher detection thresholds compared to rest, confirming previous findings. However, tactile suppression was comparable between conditions arguing against the hypothesis that it frees capacities for processing other relevant visual signals.
Keywords: ddc:150